ESG Branding Strategies in B2B And B2C Markets: Evidence From Emerging Economies - M. Ikhwan Maulana Haeruddin (Economics and Business Journal (ECBIS), 2026)
Environmental, Social, and Governance (ESG) branding has become increasingly important in strengthening stakeholder relationships and corporate legitimacy, particularly in emerging economies characterized by institutional uncertainty and diverse stakeholder expectations. However, limited studies have comparatively examined how ESG branding and communication strategies differ between business-to-business (B2B) and business-to-consumer (B2C) firms and how these differences affect relationship outcomes. This study aims to analyze the distinctions between B2B and B2C ESG communication strategies in emerging economies and their implications for stakeholder trust, loyalty, and long-term business relationships. This study employed a systematic literature review approach using evidence retrieved from the Elicit database integrating Semantic Scholar and OpenAlex sources. From an initial pool of 1,000 studies, 10 empirical articles published between 2020 and 2026 met the inclusion criteria and were analyzed using thematic synthesis. The findings reveal that B2B ESG strategies primarily emphasize governance structures, third-party ESG ratings, and verifiable sustainability metrics to strengthen interorganizational trust and reduce relational risk. In contrast, B2C ESG strategies rely more heavily on emotional storytelling, sustainability narratives, influencer engagement, and digital interaction mechanisms that enhance consumer identification, brand credibility, and loyalty. The study further demonstrates that ESG pillar salience is strongly shaped by institutional and cultural contexts rather than business model orientation alone. This study contributes to ESG and relationship marketing literature by developing a comparative framework explaining how ESG communication strategies shape stakeholder relationships across B2B and B2C environments in emerging economies.